2001
DOI: 10.1074/jbc.m102834200
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Cholesterol and Sialic Acid Content Protects Cells from the Toxic Effects of β-Amyloid Peptides

Abstract: ␤-Amyloid (A␤) is the primary protein component of senile plaques associated with Alzheimer's disease and has been implicated in the neurotoxicity associated with the disease. A variety of evidence points to the importance of A␤-membrane interactions in the mechanism of A␤ neurotoxicity and indicates that cholesterol and gangliosides are particularly important for A␤ aggregation and binding to membranes. We investigated the effects of cholesterol and sialic acid depletion on A␤-induced GTPase activity in cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 96 publications
4
96
0
Order By: Relevance
“…2A). The compactin-treatment was reported to reduce the cellular cholesterol level to about 40% of the normal level without affecting the viability [19] and we have found that inhibiting the synthesis of cholesterol reduced ganglioside content [13]. According to the decrease in ganglioside and cholesterol contents, the accumulation of hIAPP amyloids was significantly suppressed (Fig.…”
Section: Resultsmentioning
confidence: 76%
“…2A). The compactin-treatment was reported to reduce the cellular cholesterol level to about 40% of the normal level without affecting the viability [19] and we have found that inhibiting the synthesis of cholesterol reduced ganglioside content [13]. According to the decrease in ganglioside and cholesterol contents, the accumulation of hIAPP amyloids was significantly suppressed (Fig.…”
Section: Resultsmentioning
confidence: 76%
“…Lyophilized Aβ40 and Aβ42 of greater than 95% purity were obtained from American Peptide (Sunnyvale, CA) or rPeptide (Athens, GA). H13A and H14A variants of Aβ42 were obtained from rPeptide, while Aβ 1-28 , Aβ [22][23][24][25][26][27][28][29][30][31][32][33][34][35] , α-MSH, and neurotensin were obtained from American Peptide. The Aβ42 mutant M35V (21) as well as Aβ42 with an oxidized methionine (M35 OX ) (20) were kindly provided by Dr. Kevin Barnham.…”
Section: Methodsmentioning
confidence: 99%
“…When DA was used as the oxidizable substrate instead of SAPC, it was also oxidized extensively by Cu(II) and H 2 O 2 over 120 min ( Figure 4C). Aβ42, Aβ 1-28 , and Aβ [22][23][24][25][26][27][28][29][30][31][32][33][34][35] inhibited DA oxidation but not the control peptides α-MSH and neurotensin. We conclude that Aβ peptides specifically inhibit oxidation of substrates such as SAPC and DA under these conditions.…”
Section: Antioxidant Activity Of Aβ42mentioning
confidence: 99%
See 1 more Smart Citation
“…Alzheimer's disease can only be diagnosed definitively by identifying extracellular amyloid plaques composed of amyloid-β (Aβ) and neurofibrillary tangles, which consist of tau proteins, in postmortem central nervous system tissue [5,[23][24][25][26][27][28][29][30]. The main constituent of the neuritic plaques is the 39-43 amino acid peptide, β-amyloid (Aβ).…”
Section: Introductionmentioning
confidence: 99%